Applied Linguistics: CLIL and Language Learning Outcome in ESL Learners - Munir, Maryam; Ahmad, Shumaila (Pakistan Languages and Humanities Review, 2025)
The motive of this research is to dig deep down into CLIL and different techniques to incorporate in it. The term was first coined in 1994, yet there is still a lack of its implementation in Asian Educational Context .CLIL is a teaching prospective that unites teaching of Language and Content. A mixed method approach was followed and a sample size of 36 students was selected through stratified random sampling and data was analyzed through paired sample T-tests and classroom observation through thematic analysis. The result approved that CLIL is a contemporary way of teaching English Language. It is recommended that for effective incorporation of CLIL teacher’s training is a must and the use of resource materials which integrate Content and Language for better learning outcome. Different levels of competence (Reading, Writing, Speaking, Listening) must also be explored with regards to CLIL.